Convergence issues of knowledge management in digital libraries. Issue 1 (2014) - Md Anwarul Islam; Mitsuru Ikeda
<x xml:space="preserve"> Abstract </x> Purpose – Knowledge management systems have opened new arrays in the present digital environment. Nowadays, because of innumerable features, they have become the choice of many organizations. The purpose of this paper is to focus on the issues of a KM‐based digital library system that will support the creation, organization, storage, dissemination and utilization of the institution's digital knowledge assets.Design/methodology/approach – The study is based on viewpoints, a review of existing concepts and the structure of DL and KM, and on the results of an interview of ten DL practitioners world‐wide. The respondents are purposively selected from the participants' lists of an international training program (ITP) on "managing electronic information and digital libraries". The interview is conducted by e‐mail using a short, structured and open‐ended questionnaire.Findings – The present study finds some significant overlaps between DL and KM and argues that a generic KM process of acquisition, organization, storage and retrieval, and dissemination of knowledge by receiving feedback can suitably be fitted in DL. It is apparent that an integration of KM can add value to building a knowledge sharing culture, promoting the KM culture, and ultimately increase the organizational output. It helps to improve efficiency, to ensure higher productivity and user satisfaction in the library.Research limitations/implications – Further research can be conducted into designing KM‐based DL systems keeping in view the needs and behavior of the users they serve. A deep log analysis of the academically endeavored KM‐based systems can be carried out for working out a better and productive DL. The recent study requires a practical investigation.Practical implications – The outcome of the research will improve the DL system to enhance its effectiveness, staff professionalism and will help in achieving coordination. Knowledge innovation in a DL environment will help in the creation of better and an enlightened knowledge‐based society.Originality/value – The issues discussed here will help in achieving satisfaction levels both on the part of users as well as DL professionals. The proposed issues and structure is an original work and theoretically, they would contribute to the advancement of an academic debate in both the areas of DL and KM. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors are grateful to Associate Professor Jean‐Christophe Terrillon for kindly proofreading the manuscript. </ack>